Alternative management of persistent Hyperinsulinemic hypoglycemia in a neonate: A case report on octreotide and nifedipine therapy - Annia, Iva Nur; Faizi, Muhammad; Rochmah, Nur; Hisbiyah, Yuni; Perwitasari, Rayi Kurnia (Edelweiss Applied Science and Technology, 2024)
This case report highlights the successful management of Persistent Hyperinsulinemic Hypoglycemia in Infancy (PHHI) using alternative therapies, demonstrating their efficacy and practical implications in resource-limited settings. A 48-hour-old neonate presented with severe hypoglycemia unresponsive to high-dose glucose infusion. Laboratory investigations confirmed PHHI with elevated insulin and C-peptide levels. Due to the unavailability of diazoxide, treatment involved subcutaneous octreotide and oral nifedipine. The clinical course was managed and monitored according to international guidelines for hyperinsulinemic hypoglycemia. The combination therapy successfully stabilized blood glucose levels, enabling cessation of intravenous glucose infusion by day 10. The patient also recovered fully from hospital-acquired pneumonia with antibiotic treatment. These outcomes underscore the potential efficacy of nifedipine as a viable second-line therapy for PHHI in contexts where standard treatments are inaccessible. This case underscores the importance of flexible, evidence-based therapeutic approaches tailored to individual patient needs, especially in resource-constrained environments. The findings highlight nifedipine’s clinical utility in PHHI management and emphasize the need for further research, including large-scale studies, to establish standardized treatment protocols and expand access to effective therapies globally.